The lemmatization of Tshivenda lexical items - Mantsha, Avhavhudzani Virginia (University of Limpopo (Turfloop Campus), 2012)
The study focuses on the lemmatization of lexical items in Tshivenḓa. It was conducted by reviewing selected Tshivenḓa dictionaries and the lexical items investigated were nouns, locatives, verbs and adjectives. The analysis looked at the approaches used in the macro- and micro-structural treatment of these important lexical items in dictionaries. The study also covered the treatment of the morphological, syntactical and semantic aspects of these lexical items in Tshivenḓa. This research ended with recommendations that will help dictionary compilers to overcome challenges they experience when lemmatizing nouns, locatives, verbs and adjectives.
Thesis (M.A. (African Languages)) -- University of Limpopo, 2013
Keywords: Tshivenda; Lemmatization; Lexical grammar; Venda language; Language and languages - Grammars